The IRT-Buggy – Vehicle Platform for Research and Education. Issue 1 (July 2017) - Reiter, Matthias; Wehr, Matthias; Sehr, Florian; Trzuskowsky, Andreas; Taborsky, Robin; Abel, Dirk
Abstract: This paper presents the "IRT-Buggy", a model vehicle that is designed as a platform for research and education and that is developed at RWTH Aachen University. With two steered front wheels and two powered rear wheels, it can reach speeds of approx. 45km/h at a weight of slightly over 60kg. The vehicle's non-holonomous 2D kinematics are very comparable to the ones of a typical passenger vehicle. It is equipped with sensors that in similar form are also found in passenger vehicles, such as wheel speed sensors, inertial sensors and a GNSS sensor. Throughout the development of the model vehicle, special attention is paid to making the vehicle as useful as possible for control engineering tasks. For example, the electronic interfaces are designed in such a way that easy and intuitive access to all essential vehicle functions is granted while at the same time flexibility is not compromised due to oversimplification. The vehicle's operational concept allows new users to quickly operate the vehicle safely and to begin experimenting. Mechanisms are implemented that provide certain protection from maloperation. At the same time, experienced users can have full access to the actuation capabilities of the vehicle at different levels. The IRT-Buggy is intended to be usable by students in an educational context, but also to serve as a serious experimental platform for control engineering research, with no conceptual drawbacks compared to a "real" passenger vehicle other than the obvious limitations due to size, power or achievable speed.